Slavery and freedom in Savannah - Harris, Leslie M. (Leslie Maria), 1965-; Berry, Daina Ramey (The University of Georgia Press, 2013)
Slavery and Freedom in Savannah is a richly illustrated, accessibly written book modeled on the very successful Slavery in New York, a volume Leslie M. Harris coedited with Ira Berlin. Here Harris and Daina Ramey Berry have collected a variety of perspectives on slavery, emancipation, and black life in Savannah from the city's founding to the early twentieth century. Written by leading historians of Savannah, Georgia, and the South, the volume includes a mix of longer thematic essays and shorter sidebars focusing on individual people, events, and places. The story of slavery in Savannah may s.